The past, present and future of breeding rust resistant wheat - Ellis, Jeffrey G.; Lagudah, Evans S.; Spielmeyer, Wolfgang; Dodds, Peter N. (Frontiers in Plant Science, 2014)
Two classes of genes are used for breeding rust resistant wheat. The first class, called R (for resistance) genes, are pathogen race-specific in their action, effective at all plant growth stages and probably mostly encode immune receptors of the nucleotide binding leucine rich repeat (NB-LRR) class. The second class called Adult Plant Resistance genes (APR) because resistance is usually functional only in adult plants, and, in contrast to most R genes, the levels of resistance conferred by single APR genes are only partial and allow considerable disease development. Some but not all APR genes provide resistance to all isolates of a rust pathogen species and a subclass of these provides resistance to several fungal pathogen species. Initial indications are that APR genes encode a more heterogeneous range of proteins than R proteins. Two APR genes, Lr34 and Yr36, have been cloned from wheat and their products are an ABC transporter and a protein kinase, respectively. Lr34 and Sr2 have provided long lasting and widely used (durable) partial resistance and are mainly used in conjunction with other R and APR genes to obtain adequate rust resistance. We caution that some APR genes indeed include race-specific, weak R genes which may be of the NB-LRR class. A research priority to better inform rust resistance breeding is to characterize further APR genes in wheat and to understand how they function and how they interact when multiple APR and R genes are stacked in a single genotype by conventional and GM breeding. An important message is do not be complacent about the general durability of all APR genes.